Functional and technical outcomes in acute ischemic stroke patients with hyperdense middle cerebral artery sign treated with endovascular thrombectomy - Chen, Yimin; Diana, Francesco; Mofatteh, Mohammad; Zhou, Sijie; Chen, Juanmei; Huang, Zhou; Wu, Weijuan; Yang, Yajie; Zeng, Zhiyi; Zhang, Weijian; Ouyang, Ziqi; Nguyen, Thanh N.; et al. (Frontiers in Neurology, 2023)
Background and Objective: The hyperdense middle cerebral artery sign (HMCAS) is observed in a proportion of patients with acute ischemic stroke (AIS). This sign reflects the presence of an intravascular thrombus rich in red blood cells. A number of studies demonstrated that HMCAS increases the risk of poor outcomes in AIS patients treated with IV thrombolysis or no reperfusion therapy; however, whether HMCAS predicts a poor outcome in patients treated with endovascular thrombectomy (EVT) is less clear. We aimed to evaluate the functional outcome by the modified Rankin scale (mRS) at 90-days and technical challenges in patients with HMCAS undergoing EVT. Methods: We studied 143 consecutive AIS patients with middle cerebral artery M1-segment or internal carotid artery + M1 occlusions who underwent EVT. Results: There were 73 patients (51%) with HMCAS. Patients with HMCAS had a higher frequency of cardioembolic stroke (p = 0.038); otherwise, no other baseline difference was observed. No differences in functional outcome (mRS) at 90 days (p = 0.698), unfavorable outcome (mRS > 2) (p = 0.929), frequency of symptomatic intracranial hemorrhage (p = 0.924) and mortality (mRS-6) (p = 0.736) were observed between patients with and without HMCAS. In patients with HMCAS, EVT procedures were 9 minutes longer, requiring a higher number of passes (p = 0.073); however, optimal recanalization scores (modified thrombolysis in cerebral infarction: 2b-3) were equally achieved by both groups. Conclusion: Patients with HMCAS treated with EVT do not have a worse outcome at 3 months compared with no-HMCAS patients. Patients with HMCAS required a greater number of thrombus passes and longer procedure times.